Environmental right and human rights enforcement in Nigeria: visiting the nexus and a call for reform (2011)
This article examines the right to a healthy environment and human rights generally. It argues that a healthy environment is necessary for the enjoyment of other rights. It concludes and recommends that for enhanced enforcement of environmental right under Nigerian Law; it should be included in chapter IV of the 1999 Constitution.